Rates and Patterns of First-Time Admissions for Acute Coronary Syndromes across Western Australia Using Linked Administrative Health Data 2007–2015 - Forsyth, René; Sun, Zhonghua; Reid, Christopher; Moorin, Rachael (MDPI AG, 2021)
Acute coronary syndrome (ACS) is globally recognised as a significant health burden, for which the reduction in total ischemic times by way of the most suitable reperfusion strategy has been the focus of national and international initiatives. In a setting such as western Australia, characterised by 79% of the population dwelling in the greater capital region, transfers to hospitals capable of percutaneous coronary intervention (PCI) is often a necessary but time-consuming reality for outer-metropolitan and rural patients.